Encyclopedia of microbiology - Maczulak, Anne E. (Anne Elizabeth), 1954- 4 0 16; 5 (New York, NY : Facts On File, 2011)
Contains more than two-hundred cross-referenced entries and thirteen essays on topics that affect global health, industry, and the environment, covering algae, bacteria, food-borne illness, influenza, AIDS, bioterrorism, sanitation, and other related topics, and includes classifications of bacteria and archaea, a breakdown of human diseases caused by mircroorganisms, and other resources.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Microbiology -- 20 -- Encyclopedias; 20; 2